Teaching Skills of the Prospective Physical Education Teachers Based on Group Learning Commitment - Blegur, Jusuf; Lumba, Andreas J. F. (Jurnal Pendidikan Indonesia, 2022)
Micro-teaching focuses on student collaboration efforts to improve teaching skills. This focus implies that students strive and are committed to helping and supporting each other in exploring their potential through various learning experiences. The division of study groups in the micro-teaching class is an integral part to encourage collaboration between peers. However, problems still arise because all members do not commit to supporting teaching skills as the ultimate goal of micro-teaching learning.The purpose of this research is to examine the difference on the teaching skills of the prospective physical education teachers based on their group learning commitment. This research used quantitative comparative design method. Samples involved were 41 students who were programming the micro-teaching course. Data on teaching skills were collected using observation guidelines and data on group learning commitment were collected using the Organization Commitment Scale. The findings proved that those with high group learning commitment have better teaching skills than those with low group learning commitment. Group learning commitment can help students have good teaching skills through creating a comfortable feeling in learning, following up on reflection as a responsibility to improve themselves, and trying to help colleagues through the role of observer and reflection.